2013
DOI: 10.4103/0972-124x.113069
|View full text |Cite
|
Sign up to set email alerts
|

Green tea extract as a local drug therapy on periodontitis patients with diabetes mellitus: A randomized case-control study

Abstract: Background:The green tea extract is a naturally occurring product having beneficial effects that counteract with the pathobiological features of periodontitis and diabetes mellitus. Hence, the present study was aimed at incorporation of green tea extract into hydroxylpropyl methylcellulose and investigates its efficacy in chronic periodontitis patients associated with and without diabetes mellitus.Materials and Methods:For the in vitro study, formulation of green tea strips and placebo strips, and analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Various methods have been applied for the delivery of the green tea extracts. Green tea extract was incorporated into hydroxylpropyl methylcellulose [ 22 , 23 ]. This system showed a bactericidal effect against Gram-negative anaerobic rods and was effective in improving periodontal status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various methods have been applied for the delivery of the green tea extracts. Green tea extract was incorporated into hydroxylpropyl methylcellulose [ 22 , 23 ]. This system showed a bactericidal effect against Gram-negative anaerobic rods and was effective in improving periodontal status.…”
Section: Discussionmentioning
confidence: 99%
“…Adjunctive local drug therapy with thermo-reversible sustained-release green tea gel has been shown to reduce inflammation and pockets of the clinical trial in patients with chronic periodontitis [ 24 ]. It has been suggested that local drug delivery using green tea extract could be used as an adjunct in the treatment of chronic periodontitis [ 22 , 25 , 26 ]. Green tea has been added to dentifrice in previous studies [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gadagi et al 179 2013 decided to do a clinical trial testing green tea strips in patients with and without diabetes with periodontitis. They were randomly placed in strips with a placebo and with green tea in periodontal pockets.…”
Section: Natural Agentsmentioning
confidence: 99%
“…Curcumin's analgesic, anti‐inflammatory, antimicrobial, and anticarcinogenic effects have made it a mainstay in the natural system of medicine for thousands of years (Behal et al, 2011; Khezri et al, 2021; Samiei et al, 2021; Sharifi et al, 2019). Several recent studies have revealed that Curcuma extract is an effective supplement for root planning and scaling (Gadagi et al, 2013). Recent research has shown that this medication's gel and powder forms were shown to be equally effective (Pradeep et al, 2012).…”
Section: Role Of Medicinal Herbs In Dentistry and Tooth Regenerationmentioning
confidence: 99%